2018
DOI: 10.1038/s41562-018-0457-6
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of language families is shaped by the environment beyond neutral drift

Abstract: There are more than 7,000 languages spoken in the world today 1. It has been argued that the natural and social environment of languages drives this diversity 2-13. However, a fundamental question is how strong are environmental pressures, and does neutral drift suffice as a mechanism to explain diversification? We estimate the phylogenetic signals of geographic dimensions, distance to water, climate and population size on more than 6,000 phylogenetic trees of 46 language families. Phylogenetic signals of envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 40 publications
(40 reference statements)
1
57
0
Order By: Relevance
“…In order to untangle causal connections from incidental associations, we need to account for sources of covariation in our data. In particular, we need to address spatial autocorrelation and phylogenetic non-independence 3234 . Grid cells that are located near each other are likely to have similar values of climatic and landscape variables, contain related human cultures and languages, and share much of their flora and fauna.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to untangle causal connections from incidental associations, we need to account for sources of covariation in our data. In particular, we need to address spatial autocorrelation and phylogenetic non-independence 3234 . Grid cells that are located near each other are likely to have similar values of climatic and landscape variables, contain related human cultures and languages, and share much of their flora and fauna.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have reported correlations between language diversity and a number of environmental or landscape variables, there has yet to be a comprehensive global analysis. Many of these variables co-vary and tend to be clustered in space and more similar between related languages 3234 . Here, we present a global-scale analysis of language diversity that comprehensively deals with these statistical complexities.…”
Section: Introductionmentioning
confidence: 99%
“…There is now increasing evidence that a large number of features that vary widely across languages, such as specific speech sounds (e.g., Everett, Blasi & Roberts, 2015;Moisik & Dediu, 2017) or lexical or semantic categories (e.g., Language Dynamics and Change 10 (2020) 3-26 Brown & Lindsey 2004;Regier, Carstensen & Kemp, 2016) might not just reflect arbitrary cultural 'choices' , but are rather motivated by and sensitive to the specific local physical, sociocultural or technological environment (see Lupyan & Dale, 2016 for an overview). While this kind of 'linguistic adaptation' was initially suggested due to observed correlations, such as the inverse relationship between morphological complexity and population size (Lupyan & Dale, 2010), such findings are now corroborated by phylogenetic evidence suggesting that the historical diversification of language families is better explained by environmental factors such as a climate rather than neutral drift (Bentz et al, 2018;Hua et al, 2019). An ambitious paper by Blasi et al (2019) illustrates just how rigorous and transdisciplinary more recent approaches to linguistic adaptation have become: Combined results from biomechanical modeling of bite configurations with phylogenetic analyses of language change and ethnographic data suggests that changes in diet during the neolithic revolution have affected the distribution of labiodental sounds such as [f] and [v].…”
Section: 3mentioning
confidence: 92%
“…The distribution of present-day global language diversity has been shown to correlate strikingly well with several ecologically relevant variables, including climate and altitude (Bentz et al., 2018), biodiversity (Gorenflo et al., 2012; Harmon, 1996; Loh and Harmon, 2005; Moore et al., 2002; Nettle and Romaine, 2000; Sutherland, 2003), the distance from the equator (Bentz et al., 2018; Breton, 1991; Currie and Mace, 2012, 2009; Mace and Pagel, 1995; Nichols, 1999, 1990), and the length of the growing season (Nettle, 1998). A possible causal mechanism underlying these patterns was proposed by Nettle (1998, 1996), who explained a strong correlation between country-level language diversity and the length of the growing season in terms of the environmental risk hypothesis.…”
Section: Introductionmentioning
confidence: 99%